(untitled) (Journal Of Educational and Psychological Researches, 2013)
Concentrated research problem by low satisfaction of the human element, which is the mainstay key to the success of organizations and achieve their goals, so it has to be interest in it, and work to his satisfaction and the achievement of its objectives, has prevailed belief in special cases that the human element is forced to work, have resulted from that neglect, especially in the non-governmental organizations , and thus a marked decline in the performance of employees in government agencies, and thus became necessary to search for a solution of the problem and by improving satisfaction. And suffers some of the staff of the Ministry of Education, like other employees in government institutions different from the low level of satisfaction, because of the lack of salaries of some, especially in the lower ranks, and do not put them in the right place or the practice of their specialty, non-distribution of jobs according to their abilities, aptitudes and interests, and inequity in the distribution of promotions, incentives and bonuses Incentive pay scale, and the way to deal with management, which may reflect negatively on the quality of performance in these General Directorates of Education. Accordingly, the research question can be formulated as follows: - To what extent job satisfaction among employees of the Ministry of Education in the Directorate General for Education in the provinces? The importance of research originate of the General Directorates of Education is pivotal in the areas of its presence, as it oversees all activities, and provides educational services to a wide range of educational institutions and students in their geographical boundaries, as well as the quality of the performance of employees and morals and loyalty to their institutions and their duties professional and educational about their depends on the a Harmony of their work and their sense of comfort and stability in the course of their work, which drives them to improve their productivity and quantity. Either the objectives of the research have focused to identify the impact of factors of job satisfaction following (job satisfaction, satisfaction with pay, satisfaction with the method of management and supervision, satisfaction with pay, growth and upgrading, stability in work) on the performance of employees, and provide suggestions and recommendations that will help to raise the level Job satisfaction in the General Directorates of Education for all provinces (except Kurdistan). Either the most important recommendations reached by the search 1 - to strengthen the relationship between senior management and staff to contribute to the integration of the employee with his constituency through mutual respect, appreciation and fruitful cooperation, and teamwork. 2 - Develop a system of rewards and incentives to ensure full justice to employees, so as to reward outstanding and to hold negligent in his work, because it encourages employees to deliver the best.